Travelling the Korosko Road : archaeological exploration in Sudan's Eastern Desert - Davies, W. V.,; Welsby, Derek A., (Sudan Archaeological Research Society publication ;, 2020)
This volume publishes accounts of archaeological exploration carried out in the Sudanese Eastern Desert. A pioneering programme of expeditions along the so-called 'Korosko Road' revealed a rich archaeological landscape frequented over millennia, including gold-production areas and their associated settlements.